(untitled) (International Journal of Culture and Art Studies, 2020)
This research aims to study the novel illustration as a sign in Harry Potter and The Prisoner of Azkaban novel by J.K. Rowling (2014). The researcher shows how the illustrations can influence readers by illustrating images, events, colors, and the typography displayed on the novel’s cover. This research is qualitative. The data source used is the Harry Potter and The Prisoner of Azkaban novel by J.K. Rowling (2014) UK edition. The data collection technique is from analyzing the novel illustration.Â The theory used in this study is a semiotic analysis of literature, the course of the sign, meaning, metaphor, and symbolism.Â The result of this study are as follows: first, the value of novel illustrations. Second, the meaning of color psychology. Third, the reviews about the different edition of Harry Potter and The Prisoner of Azkaban novel.